2017
DOI: 10.1161/circinterventions.116.004924
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Catheter-Based Reinterventions Are Common in Long-Term Survivors of the Fontan Operation

Abstract: Background— There are limited follow-up studies examining surgical and catheter-based reinterventions in long-term survivors of the Fontan operation. Methods and Results— All 773 patients who underwent Fontan at our institution between 1992 and 2009 were retrospectively reviewed. Current information regarding post-Fontan intervention was available for 70%. By 20 years after Fontan, 65% of patients had experienced either surgical or transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…There are only scarce data on rate of reintervention after Fontan in contemporary cohorts. Our data are comparable to the rate of 31% surgical and 47% catheter-based reinterventions observed in the series of Philadelphia at 15 years, and 28% surgical and 57% catheter reinterventions occurring over a 15-year study period in the repeated cross-sectional study of the Paediatric Heart Network study 3 7. Fifteen per cent (214/1428) of our patients required a catheter-based intervention.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There are only scarce data on rate of reintervention after Fontan in contemporary cohorts. Our data are comparable to the rate of 31% surgical and 47% catheter-based reinterventions observed in the series of Philadelphia at 15 years, and 28% surgical and 57% catheter reinterventions occurring over a 15-year study period in the repeated cross-sectional study of the Paediatric Heart Network study 3 7. Fifteen per cent (214/1428) of our patients required a catheter-based intervention.…”
Section: Discussionsupporting
confidence: 82%
“…The Fontan procedure is often described as the last in a series of procedures performed for single ventricle palliation. As this growing population ages, it is increasingly being recognised that this population will require intensive follow-up and numerous interventional catheterisation procedures and repeated cardiac surgery procedures 1–3. However, the incidence of these reinterventions, their nature and, more importantly, their consequences are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some studies have found a single ventricle of left morphology to be a risk factor, 5,6 but others have not. 7,8 The risk for permanent pacemaker implantation was found to be higher after LT than EC in one study, 6 but this was not confirmed in other studies in which LT was not associated with a higher risk of pacemaker than EC, at least not after adjusting for time after Fontan surgery. 2,3,9 Patients with Fontan circulation and concomitant pacemaker implantation have been shown to be at higher risk for adverse events, such as death or heart transplantation.…”
Section: Introductionmentioning
confidence: 89%
“…In most cases, neonatal surgery is performed to ensure sufficient blood sup- Previous studies have reported the need for permanent pacemaker implantation in 7%-25% of patients who undergo Fontan surgery. 2,[4][5][6] The risk of pacemaker treatment has been shown to increase with time after Fontan surgery. 5 Some studies have found a single ventricle of left morphology to be a risk factor, 5,6 but others have not.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac care teams have long sought factors that impact both short-and long-term outcomes of patients with univentricular physiology who undergo the Fontan procedure. [1][2][3][4] The surgical advances in performing the Fontan procedure, including staged palliation and its modification (ie, fenestration), have further complicated our quest for understanding. In this issue of the Journal, Ono and colleagues 5 approach this question by focusing on intensive care unit length of stay (ICU-LOS), factors associated with ICU-LOS, and the relationship between ICU-LOS and late outcomes.…”
mentioning
confidence: 99%